Denver landmarks and historic districts - Noel, Thomas J., author; Wharton, Nicholas J., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
The newest and most thorough guide to Denver's 52 local historic districts with over 300 individually landmarked properties. This lavishly illustrated volume celebrates Denver's oldest banks, churches, clubs, hotels, libraries, schools, restaurants, mansions, and show homes.
Central Denver -- Capitol Hill area -- Northeast Denver -- Northwest Denver -- South Denver -- East Denver -- Denver mountain parks landmarks.
Second edition.
Keywords: Denver (Colo.) -- Guidebooks; Historic sites -- Colorado -- Denver -- Guidebooks